قلق المستقبل وعلاقته بمستوى الطموح لدى عينة من طلبة الدكتوراه- دراسة مقارنة بين طلبة الدكتوراه كلاسيك وطلبة الدكتوراه نظام جديد - بوراس حورية; عرعار سامية (biblio centrale, université laghouat, 2018)
The present study aims to reveal the relation between the Future anxiety and the level of Aspiration of PhD students (classical system and new system), the study also seeks to know the differences between both systems’ students’ averages at the level of Future anxiety and the level of Aspiration in the following demographic variables: (gender, year registration in PhD, faculty) We conducted the study in all the faculties of Ammar Thledji University (Laghouat) on a sample of 317 PhD students in both systems. The study aims to answer the following questions: - Is there a correlation between the Future anxiety and the level of Aspiration in a sample of doctoral students belonging to both systems (classical, new system) at the University of Laghouat? - Are there statistically significant differences between the average of both the classical system’s students and the new system’s (LMD) students at the high level of future anxiety in a sample of doctoral students at Laghouat University? - Are there statistically significant differences between the average scores of classical system’s students and the new system’s (LMD) students in the high level of Aspiration of doctoral students’ sample at Laghouat University? - Are there statistically significant differences between the average scores of classical system’s students and the new system’s students (LMD) at the level of Future anxiety due to the following variables: gender (male / female), year of registration for PhD, faculty in a sample of doctoral students at Laghouat University? - Are there statistically significant differences between the average scores of classical system’s students and the new system’s students (LMD) in the level of Aspiration due to the following variables: gender (male / female), year of registration, faculty in a sample of doctoral students at Laghouat University? The researcher used the descriptive approach with its comparative method. She used two standards. The first standard measures the Future anxiety made by the researcher herself and the second measures the level of Aspiration by Kamilia Abd El-Fattah (1975). The statistical processing was done by the statistical package for services and solutions( spss ) version 17 and we obtained the following results: - There is a positive correlation between Future anxiety and the level of Aspiration among the sample of PhD students from both systems (classic, new systems) at Laghouat University .- Both systems’ PhD students suffer from high level of Future anxiety. - Both systems’ PhD students possess a high level of Aspiration. - There are statistically significant differences between the average scores of classical system’s students and the new system’s students (LMD) at the level of Future anxiety regarding the gender variable (male / female) in favor of females. - There were no statistically significant differences between the average scores of classic system’s students and the new system’s students (LMD) in the level of Aspiration attributed to the gender variable (male / female) in a sample of doctoral students at Laghouat University. - There were no statistically significant differences between the average scores of the students of the classical system and the students of the new system (LMD) at the level of Future anxiety due to the change in the year of registration of a sample of doctoral students at Laghouat University. - There were no statistically significant differences between the average scores of students of the classical system and the students of the new system (LMD) in the level of Aspiration due to the change in the year of registration in the doctorate in a sample of doctoral students at Laghouat University. -There were no statistically significant differences between the average scores of students of the classical system and the students of the new system (LMD) at the level of Future anxiety due to the faculty variable (humanities, social sciences, science, technology, arts and languages, rights, political sciences, economics and management sciences) of the doctoral students at Laghouat University. - There are no statistically significant differences between the average scores of classical system’s students and the new system’s students (LMD) in the level of Aspiration attributed to the faculty variable (human and social sciences, science, technology, arts and languages, rights, political science, economics and management sciences) of the doctoral students at Laghouat University.